Explaining the larger seed bank of an invasive shrub in non-native versus native environments by differences in seed predation and plant size - Bakker, Mark R (Ann Bot, 2019)
BACKGROUND AND AIMS: Large, persistent seed banks contribute to the invasiveness of non-native plants, and maternal plant size is an important contributory factor. We explored the relationships between plant vegetative size (V) and soil seed bank size (S) for the invasive shrub Ulex europaeus in its native range and in non-native populations, and identified which other factors may contribute to seed bank variation between native and invaded regions. METHODS: We compared the native region (France) with two regions where Ulex is invasive, one with seed predators introduced for biological control (New Zealand) and another where seed predators are absent (La Réunion). We quantified seed bank size, plant dimensions, seed predation and soil fertility for six stands in each of the three regions. KEY RESULTS: Seed banks were 9–14 times larger in the two invaded regions compared to native France. We found a positive relationship between current seed bank size and actual plant size, and that any deviation from this relationship was probably due to large differences in seed predation and/or soil fertility. We further identified three possible factors explaining larger seed banks in non-native environments: larger maternal plant size, lower activity of seed predators and higher soil fertility. CONCLUSIONS: In highlighting a positive relationship between maternal plant size and seed bank size, and identifying additional factors that regulate soil seed bank dynamics in non-native ranges, our data offer a number of opportunities for invasive weed control. For non-native Ulex populations specifically, management focusing on ‘S’ (i.e. the reduction of the seed bank by stimulating germination, or the introduction of seed predators as biological control agents) and/or on ‘V’ (i.e. by cutting mature stands to reduce maternal plant biomass) offers the most probable combination of effective control options.